2010
DOI: 10.1002/chem.200901758
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Complex of [Ru(tpm)(dppz)py]2+ with a B‐DNA Oligonucleotide—A Single‐Substituent Binding Switch for a Metallo‐Intercalator

Abstract: We report the synthesis of three new complexes related to the achiral [Ru(tpm)(dppz)py](2+) cation (tpm=tripyridazole methane, dppz=dipyrido[3,2-a:2',3'-c]phenazine, py=pyridine) that contain an additional single functional group on the monodentate ancillary pyridyl ligand. Computational calculations indicate that the coordinated pyridyl rings are in a fixed orientation parallel to the dppz axis, and that the electrostatic properties of the complexes are very similar. DNA binding studies on the new complexes r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 56 publications
3
35
0
Order By: Relevance
“…However, it should be noted that a much higher slope of 0.85 was reported for the analogous [(tpm)RhCl(dppz)]Cl 2 complex. [12] A lower slope value of 0.34 is observed for the dpq complex, in accord- [31,32] for UV/ Vis titration data of [( [9] ance with the findings of the 1 H NMR and UV/Vis titrations, and indicates a weaker intercalative binding mode for 7. Competition between intercalation and alternative groove-binding or covalent-binding modes cannot be ruled out on the basis of this evidence.…”
Section: Peptide and Dna Binding Studiessupporting
confidence: 85%
See 1 more Smart Citation
“…However, it should be noted that a much higher slope of 0.85 was reported for the analogous [(tpm)RhCl(dppz)]Cl 2 complex. [12] A lower slope value of 0.34 is observed for the dpq complex, in accord- [31,32] for UV/ Vis titration data of [( [9] ance with the findings of the 1 H NMR and UV/Vis titrations, and indicates a weaker intercalative binding mode for 7. Competition between intercalation and alternative groove-binding or covalent-binding modes cannot be ruled out on the basis of this evidence.…”
Section: Peptide and Dna Binding Studiessupporting
confidence: 85%
“…The model assumes non-cooperative, nonspecific binding with the existence of one type of discrete binding 3 + , where tpm = tris(pyrazolyl)methane, py = pyridine, H 2 metOMe = l-methionyl methyl ester, respectively. [31,32] The…”
Section: Peptide and Dna Binding Studiesmentioning
confidence: 98%
“…Recent crystal and NMR structure studies of monomeric Ru II compounds interacting with oligonucleotide duplexes suggest that intercalation is sequence dependent, and that additional binding sites on the DNA may be exploited 8. 9…”
Section: Introductionmentioning
confidence: 99%
“…[7] Recent crystal and NMR structure studies of monomeric Ru II compounds interacting with oligonucleotide duplexes suggest that intercalation is sequence dependent, and that additional binding sites on the DNA may be exploited. [8,9] Abstract: Binuclear polypyridine ruthenium compounds have been shown to slowly intercalate into DNA, following a fast initial binding on the DNA surface. For these compounds, intercalation requires threading of a bulky substituent, containing one Ru II , through the DNA base-pair stack, and the accompanying DNA duplex distortions are much more severe than with intercalation of mononuclear compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Although the 3‐pyNH 2 ‐based complex binds by intercalation with affinities that are comparable to the parent compound, the coordinated 4‐pyNH 2 complex is a low affinity, non‐intercalating, groove binder. NMR studies revealed that this is due to unfavourable interactions made by the 4‐NH 2 of the coordinated pyridine projecting into the minor groove of the duplex . This suggests that 4‐py‐based connectivity within the tether of 6 may have an unfavourable effect on its binding characteristics.…”
Section: Introductionmentioning
confidence: 99%